The short-term association of PM2.5 and stroke: a time-stratified case-crossover study in Berlin, Germany - Jakob Beilstein; David Q. Rich; Heinrich J. Audebert; Toivo Glatz (Air Quality, Atmosphere & Health, 2026)
Exposure to fine particulate matter (PM 2.5 ) is a major, potentially preventable contributor to cardiovascular disease and death. PM 2.5 levels in many urban regions, including Berlin, exceed recommended thresholds. We assessed whether short-term PM 2.5 exposure is associated with ischemic stroke and transient ischemic attacks (TIA) in Berlin, Germany (2017–2020). We linked a population-based stroke registry with hourly PM 2.5 and meteorological measurements and applied a time-stratified case-crossover design with conditional logistic regression, adjusting for meteorological and time-varying factors (public holidays, pandemic period indicator). Associations were estimated at symptom onset and for the preceding 36 h using hourly lags. Among 9,565 ischemic stroke and TIA cases, a one-standard-deviation increase in PM 2.5 (10.28 µg/m 3 ) increased the odds of stroke occurrence by 2% (adjusted OR (aOR) 1.020, 95% CI [0.994, 1.047]). Lagged estimates showed a wave-like pattern with irregular peaks, whereby the second largest estimate occurred 18 h before symptom onset (aOR = 1.015, 95% CI [0.989, 1.042]). These findings are consistent with previously reported adverse short-term cerebrovascular effects of PM 2.5 . Although associations were modest and imprecise, PM 2.5 exposure is widespread and largely unavoidable in urban settings, so further reductions may yield population health benefits. This study investigated hourly lagged exposure, indicating that associations vary preceding symptom onset. Replication and pooled multi-city analyses with comparable high-resolution data are needed to more precisely identify critical exposure windows and to quantify benefits of further PM 2.5 reductions under tightened air quality guidelines.